Examining the Effects of Intensive Supervision and Aftercare Programs for At-Risk Youth: A Systematic Review and Meta-Analysis. (May 2018) - Bouchard, Jessica; Wong, Jennifer S.
Community correctional sentences are administered to more juvenile offenders in North America than any other judicial sentence. Particularly prominent in juvenile corrections is intensive supervision probation and aftercare/reentry, yet the effects of these supervision-oriented interventions on recidivism are mixed. The purpose of this meta-analysis is to determine the effects of intensive supervision probation and aftercare/reentry on juvenile recidivism. An extensive search of the literature and application of strict inclusion criteria resulted in the selection of 27 studies that contributed 55 individual effect sizes. Studies were pooled based on intervention type (intensive supervision probation or aftercare/reentry) and outcome measure (alleged or convicted offenses). The pooled analyses yielded contradictory results with respect to outcome measure; in both cases, supervision had a beneficial effect on alleged offenses and negatively affected convicted offenses. These patterns across intervention type and outcome measure, as well as recommendations for future research, are discussed.